The Usborne first encyclopedia of seas and oceans - Denne, Ben. (London : Usborne ; Tilsa, Okla. : EDC, 2011)
Illustrations and simple text introduce young readers to the wonders of the seas and oceans, describing the different plants and fish that can be found under water and providing a list of Web sites which offer more information.
Cover title: Usborne Internet-linked first encyclopedia of seas & oceans.
Includes index.
4.7
3-6.
3-6
Keywords: Marine ecology -- Juvenile literature; Ocean -- Juvenile literature; Marine ecology; Ocean; Marine ecology; Ocean